Addition of azathioprine to the switch of anti-TNF in patients with IBD in clinical relapse with undetectable anti-TNF trough levels and antidrug antibodies: a prospective randomised trial. Issue 7 (24th January 2020) - Roblin, Xavier; Williet, Nicolas; Boschetti, Gilles; Phelip, Jean-Marc; Del Tedesco, Emilie; Berger, Anne-Emmanuelle; Vedrines, Philippe; Duru, Gerard; Peyrin-Biroulet, Laurent; Nancey, Stéphane; Flourie, Bernard; Paul, Stephane
Abstract : Objectives: In patients with IBD experiencing an immune-mediated loss of response (LOR) to antitumour necrosis factor (anti-TNF), algorithms recommend a switch of anti-TNF without immunosuppressive drug. The aim of our study was to compare in these patients two strategies: either switch to a second anti-TNF alone or with addition of azathioprine (AZA). After randomisation outcomes (time to clinical and pharmacokinetic failure) were compared between the two groups during a 2-year follow-up period. Design: Consecutive IBD patients in immune-mediated LOR to a first optimised anti-TNF given in monotherapy were randomised to receive either AZA or nothing with induction by a second anti-TNF in both arms. Clinical failure was defined for Crohn's disease (CD) as a Harvey-Bradshaw index ≥5 associated with a faecal calprotectin level >250 µg/g stool and for UC as a Mayo score >5 with endoscopic subscore >1 or as the occurrence of adverse events requiring to stop treatment. Unfavourable pharmacokinetics of the second anti-TNF were defined by the appearance of undetectable trough levels of anti-TNF with high antibodies (drug-sensitive assay) or by that of antibodies (drug-tolerant assay). Results: Ninety patients (48 CDs) were included, and 45 of them received AZA after randomisation. The second anti-TNF was adalimumab or infliximab in 40 and 50 patients, respectively. Rates of clinical failure and occurrence of unfavourable pharmacokinetics were higher in monotherapy compared with combination therapy (p<0.001; median time of clinical failure since randomisation 18 vs >24 months). At 24 months, survival rates without clinical failure and without appearance of unfavourable pharmacokinetics were respectively 22 versus 77% and 22% versus 78% (p<0.001 for both) in monotherapy versus combination therapy. Only the use of combination therapy was associated with favourable outcomes after anti-TNF switch. Conclusion: In case of immune-mediated LOR to a first anti-TNF, AZA should be associated with the second anti-TNF. Trial registration number: 03580876.